Teoria da aprendizagem significativa : análise de um curso de formação continuada para professores de biologia - Rezende, Mary Carneiro (2015)
Studies indicate that the teaching of Biology occurs even in a Cartesian way, inducing learners to develop little critical thinking and, consequently, learning happens in a superficial way and, often, mechanical way, which implies difficulties of articulation between scientific knowledge and of these with the social world in which they live. Furthermore, in a collective analysis of their own practice and monitoring records and observations in the continuing education of those municipalities, it is realized that little progress has been made in specific studies of the disciplines and/or areas. In this context the problem for the development of this research was the following: how implementing the theory of meaningful learning-TML can contribute to continued training of Biology teachers that work in the High School of the State Public Schools of Barra do Garças and Pontal do Araguaia/MT? From this inquiry, we developed a study of qualitative paradigm, the case study, with seven teachers of biology that work in these municipalities. For such action, it was developed a educational product: Syllabus (Didatic Plan), which was implemented in a course, with hour load of 60h. This work aimed to analyze a course of continued education for Biology teachers. With the analysis of the data, it could infer that the educational product contributed in overcoming some gaps from initial training and for the reflection of the pedagogical practice. In summary, the data indicate paths for changes in the pedagogical practices of the subjects researched.